Experimental study of conventional wire electrical discharge machining for microfabrication - Ali, Mohammad Yeakub; Mohammad, Ammar Sami (Taylor and Francis Inc., 2008)
This article discusses the investigation and optimization of the process parameters of conventional wire electrical discharge machining (WEDM) of a copper substrate for microfabrication. The effect of discharge current, pulse-on time, and gap voltage on surface finish were studied. The average surface roughness (R a ) and peak-to-valley height (R t ) were measured with a surface profiler. The surface roughness increased with higher discharge current and gap voltage. With the increase of pulse-on time, the surface roughness decreased. Statistical models were established to predict the surface roughness R a and R t in terms of discharge current, pulse-on time, and gap voltage. Using the optimized parameters, miniaturized spur gears, and plate-shaped hot embossing microtools were fabricated where an average surface roughness of about 1 µ m and dimensional accuracy of 1–2% were achieved.